Long-term results of antiviral therapy in patients with chronic hepatitis C with sustained virologic response - T. M. Ignatova; T. N. Lopatkina; V. P. Chulanov; Ye. V. Gaydasheva; S. N. Batskikh; G. V. Mikhaylovskaya; D. T. Abdurakhmanov; S. Yu. Karpov; Ye. N. Nikulkina; O. A. Chernova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2013)
Aim of investigation. To estimate frequency of late relapses and clinical outcomes in patients with chronic hepatitis C (CHC) with sustained virologic response (SVO) achievement at antiviral therapy (AVT).Material and methods. Overall 208 patients with CHC, including 12 at the stage of liver cirrhosis (LC), who achieved SVO were investigated. Mean duration of the follow-up was 56,1±35,4 months. Standard clinical and laboratory investigation and evaluation of RNA HCV was carried out. In 114 patients RNA HCV and DNA HBV in blood serum and peripheral mononuclear blood cells were studied by polymerase chain reaction (PCR) with fluorescent hybridization detection in «real time» mode (sensitivity of 10 IU/ml for HCV and 5 IU/ml for HBV).Results. In 3 (1,5%) patients late (i.e. over 6 months after AVT) relapses of HCV-infection were observed. Application of ultraresponsive PCR method allowed to reveal relapse half a year prior to its clinical and laboratory manifestation in 2 cases. No data on latent HCVinfection was obtained not in a single case, including patients with relapse of cryoglobulinemia syndrome. A principal cause of elevation of alanine transaminase activity was non-alcoholic steatohepatitis. In one LC patient development of esophageal varicose veins was detected. There were no cases of decompensation of LC, hepatocellular carcinoma and death due to liver disease.Conclusion. At patients who have achieved SVO as a result of AVT, late relapses of HCV-infection are rare and in the majority no disease progression was found. Relapses of cryoglobulinemia syndrome were observed, but data on presence of latent HCV-infection were not received. Highly sensitive PCR methods are rational for assessment of SVO.